Kaizen and continuous improvement – trends and patterns over 30 years. Issue 4 (21st June 2018) - Carnerud, Daniel; Jaca, Carmen; Bäckström, Ingela
Abstract : Purpose: The purpose of this paper is to depict how Kaizen and continuous improvement (CI) are represented in scientific journals focusing on quality management (QM) from the 1980s until 2017. Additionally, the study aims to examine how Kaizen is studied and described and how the relationship between Kaizen and CI is portrayed. Design/methodology/approach: The study applies a mixed methods approach to search for tendencies and outlines concerning Kaizen and CI in four scientific journals focusing on QM and two focusing on OM. The data set contains entries from 1980 until 2017, which makes it possible to depict how Kaizen has evolved over more than 30 years. Findings: The findings show that Kaizen and CI attained special interest in the mid-1990s, after which interest appears to have decreased. However, the findings imply that a regenerated interest for the areas spiked post 2010. In addition, the results indicate that Kaizen is on the one hand accepted by one part of the management community but on the other hand completely ignored by the rest. Finally, the data illuminate a need to strengthen and clarify Kaizen's theoretical basis and its relationship to CI. Practical implications: If an aspiration exists to increase the success rate of Kaizen implementation, the results from the study highlight the need to address and clarify epistemological, terminological and theoretical issues. Originality/value: Prior data mining studies pinpointing how Kaizen and CI have evolved over the last 30 years appear not to exist.